2013
DOI: 10.5194/acpd-13-28561-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation and modelling of HO<sub>x</sub> radicals in a boreal forest

Abstract: Measurements of OH and HO2 radicals were conducted in a pine-dominated forest in southern Finland during the HUMPPA-COPEC-2010 (Hyytiälä United Measurements of Photochemistry and Particles in Air -Comprehensive Organic Precursor Emission and Concentration study) field campaign in summer 2010. Simultaneous side-by-side measurements of hydroxyl radicals were conducted with two instruments using chemical ionization mass spectrometry (CIMS) and laser-induced fluorescence (LIF), indicating small systematic disagree… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…(Junninen et al, 2009). Further details and a more complete description of the site, the instrumentation, and the meteorological conditions during the campaign can be found in Williams et al (2011) and Hens et al (2014). A brief description of the instruments used in this study is given here.…”
Section: Measurement Site and Ancillary Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…(Junninen et al, 2009). Further details and a more complete description of the site, the instrumentation, and the meteorological conditions during the campaign can be found in Williams et al (2011) and Hens et al (2014). A brief description of the instruments used in this study is given here.…”
Section: Measurement Site and Ancillary Instrumentationmentioning
confidence: 99%
“…The OH calibration of the HORUS instrument is obtained via the production of a known amount of OH and hydroperoxyl radicals (HO 2 ) from the photolysis of water at 185 nm using a mercury lamp. A more detailed description of the instrument calibration is reported by Martinez et al (2010) and Hens et al (2014). A calibration factor for the background OH signal observed by the HORUS instrument is currently not available.…”
Section: Ipi-lif-fage Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Field studies, in which OH reactivity was dominated by monoterpenes, showed that models underestimate HO 2 and OH concentrations (Kim et al, 2013;Hens et al, 2014). A chamber study investigating the photochemistry of β−pinene found that an additional HO 2 source is required to explain observed HO 2 and OH and suggested a rearrangement of radical intermediates as explanation (Kaminski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%